Recidivism among people sentenced to community service in Finland - Muiluvuori, Marja-Liisa (Journal of Scandinavian studies in criminology and crime prevention, 2001)
The influence of community service on recidivism is studied by comparing the subsequent recidivism of people sentenced to community service with the recidivism of people sentenced to prison for a maximum of 8 months. The distributon of sex, age, principal offence, times in prison and length of sentence in the prison group was analogous to that of the community service group. The follow-up period was 5 years. The analysis shows, compared to recidivism after prison sentences, was slightly lower. In the light of this, community service seems to be a suitable sanction in particular for sentenced people lacking previous prison experience